2020
DOI: 10.51273/esc20.251633
|View full text |Cite
|
Sign up to set email alerts
|

A Morphological Study on Gross Anatomical Variations of Embalmed Cadaveric Livers

Abstract: Objective: To find out gross anatomical variations of embalmed cadaveric livers. Methods: Present study was conducted in dissection halls of Anatomy departments of Allama Iqbal Medical College, Lahore, Sahiwal Medical College, Sahiwal and Fatima Jinnah Medical University, Lahore during 2016-2019. In this study, 74 livers were dissected out from embalmed cadavers and preserved in 10% formalin. Different morphological variations were observed in livers which included presence of accessory lobes, accessory sulci,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Wahane and Satpute and Anbumani et al found lingular process in 4% and 6.6% of livers, respectively [ 16 , 17 ]. The incidence was 2.7% and 1.81% in the study by Zahid et al and Nayak, respectively [ 18 , 19 ]. Mamatha et al found the maximum number of lingular processes among these studies at 21.3% [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wahane and Satpute and Anbumani et al found lingular process in 4% and 6.6% of livers, respectively [ 16 , 17 ]. The incidence was 2.7% and 1.81% in the study by Zahid et al and Nayak, respectively [ 18 , 19 ]. Mamatha et al found the maximum number of lingular processes among these studies at 21.3% [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 17.14% of livers had an accessory lobe which was similar to the study by Saritha et al with 16% of cases [ 28 ]. Aliya et al found it in 10.8% of livers [ 18 ]. Mehare et al reported it in 6% of cases [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation